Pretreatment, modification and applications of sewage sludge-derived biochar for resource recovery- A review. (January 2022) - Xiao, Yao; Raheem, Abdul; Ding, Lu; Chen, Wei-Hsin; Chen, Xueli; Wang, Fuchen; Lin, Sheng-Lun
Abstract: With the quick increase in industrialization and urbanization, a mass of sludge has been produced on the account of increased wastewater treatment facilities. Sewage sludge (SS) management has become one of the most crucial environmental problems because of the existence of various pollutants. However, SS is a carbon-rich material, which has favored novel technologies for biochar production, which can be utilized for dissimilar applications. This review systematically analyzes and summarizes the pretreatment, modification, and especially application of sewage sludge-derived biochar (SSBC), based on published literature. The comparative assessment of pretreatment technology such as pyrolysis, hydrothermal carbonization, combustion, deashing, and co-feeding is presented to appraise their appropriateness for SS resource availability and the production of SSBC. In addition, the authors summarize and analyze the current modification methods and divide them into two categories: physical properties and surface chemical modifications. The applications of SSBC as absorbent, catalyst and catalyst support, electrode materials, gas storage, soil amendment, and sold biofuel are reviewed in detail. Furthermore, the discussion about the existing problems and the direction of future efforts are presented at the end of each section to envisage SS as a promising opportunity for resources rather than a nuisance. Graphical abstract: Image 1 Highlights: Pretreatment technologies of sewage sludge-derived biochar (SSBC) were reviewed. A comparison study of well-known pretreatment technologies was presented. Modification method and activation mechanism of SSBC were summarized and analyzed. Various applications of SSBC were systematically reviewed and analyzed. More attention should be paid to the potentially harmful influence of SSBC.